2013
DOI: 10.1021/jo302696y
|View full text |Cite
|
Sign up to set email alerts
|

Vinylogous Reactivity of Enol Diazoacetates with Donor–Acceptor Substituted Hydrazones. Synthesis of Substituted Pyrazole Derivatives

Abstract: A regiospecific synthesis of multi-functional pyrazoles has been developed from a cascade process triggered by Rh(II)-catalyzed dinitrogen extrusion from enoldiazoacetates with vinylogous nucleophilic addition followed by Lewis acid catalyzed cyclization and aromatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…We rationalized that the formation of the regioisomeric [4+3] cycloadduct 13 a was most likely caused by a competing reaction of the diene occurring at the vinylogous position of the carbenoid, thus generating a zwitterionic intermediate, which then cyclizes to 13 a. [7][8][9] Previous studies have shown that vinylogous reactivity is favored in polar solvents. [7] Indeed, when the reaction was repeated using dichloromethane as the solvent, the ratio of 12 a to 13 a improved to 87:13, and the regiosiomeric [4+3] cycloadduct 13 a was produced in 71 % ee.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…We rationalized that the formation of the regioisomeric [4+3] cycloadduct 13 a was most likely caused by a competing reaction of the diene occurring at the vinylogous position of the carbenoid, thus generating a zwitterionic intermediate, which then cyclizes to 13 a. [7][8][9] Previous studies have shown that vinylogous reactivity is favored in polar solvents. [7] Indeed, when the reaction was repeated using dichloromethane as the solvent, the ratio of 12 a to 13 a improved to 87:13, and the regiosiomeric [4+3] cycloadduct 13 a was produced in 71 % ee.…”
mentioning
confidence: 83%
“…Chemie quent cyclization to the cycloheptadiene 25 is faster than bond rotation. Zwitterionic intermediates have been shown to be likely in several types of stereoselective reactions of rhodium vinylcarbenes, [8] so the concept of rapid cyclization of zwitterionic intermediates without epimerization is well established. Both the diene and the vinylcarbenoid would need to react through an s-cis conformation for ring closure to occur without bond rotation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when donor/acceptor-substituted hydrazones ( N -aryl hydrazonoacetates) were used instead of diarylhydrazones 42 , a series of pyrazole derivatives were formed via dirhodium(II)-catalyzed vinylogous addition followed by Lewis acid-catalyzed cyclization and aromatization. 134 …”
Section: Mecc Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
“…The vinylogous reactivity of rhodium carbenoids derived from vinyl-diazoacetates, including those without [39,40] and those with [29,32,41,42] a substituent at the vinyl terminus, is known and has been discussed. Among other factors, this vinylogous carbenoid reactivity is favored with bulky substrates and bulky ligands on the rhodium catalyst [29,32], furthermore by the use of diruthenium(I,I) [43] and silver catalysts.…”
Section: Reactions Of Styryl-diazoacetatementioning
confidence: 99%